Spatial modeling reveals a growing threat to the world's largest rhodolith beds. (1st February 2023) - Santos, Viviane S. dos; Moura, Rodrigo L. de; Magdalena, Ulises R.; Hovey, Renae; Kendrick, Gary; Bahia, Ricardo G.; Amado-Filho, Gilberto M.; Siqueira, Marinez F. de
Abstract: Rhodolith beds comprise a highly biodiverse and productive ecosystem that dominates the mid and outer shelf of the tropical eastern South American coast. Conservation planning and specific conservation measures are lacking, while impacts over rhodolith beds are escalating due to carbonate mining, and other activities such as oil and gas exploration and seaport dredging. Primary data detailing the spatial extent and characteristics of rhodolith beds within the Brazilian Economic Exclusive Zone (EEZ) depend on extensive acoustic surveys and ground truthing, which are costly and logistically challenging. Here, we compiled an extensive database of rhodolith occurrence from the scientific and grey literature. 'Ensemble' Ecological Niche Modelling (EENM) techniques predicted the total area suitable for rhodoliths across the Brazilian EEZ and gave insight into the environmental variables driving their distribution in this region. Using the suitability map produced from the ensemble model, we compared rhodolith spatial overlap with oil and gas and mining activities and marine protected areas (MPAs). Light, saturation state of calcite and minimum temperature were the main predictors of rhodolith occurrence. Rhodoliths were predicted to occur over ∼167, 379 km 2 of the Brazilian EEZ largely (∼95%) in the Amazonas (AM), Northeastern Brazil (NB) and Eastern Brazil (EB) ecoregions. The representation of rhodoliths in areas with mining and oil and gas activities was similar for the EEZ as a whole. Within each ecoregion, representation of rhodolith beds in MPAs is negatively related with their overlap with mining and oil and gas activities. Eastern Brazil (EB) stood out as the area with the highest representation of rhodoliths under threat, in an area 6.7 times larger than those represented in MPAs, including the south region of the largest continuous extension of rhodolith beds, in the Abrolhos bank. Within the NB and AM ecoregions, which are under growing industrialization, rhodolith beds are poorly represented in no-take MPAs. Our results provide a basis for moving toward more effective management and conservation strategies for rhodolith beds in Brazil's EEZ. Highlights: 'Ensemble' Ecological Niche Modelling increasing accuracy of rhodolith suitability. Rhodolith occurrence limited by minimum temperature and light. Optimization of suitable areas with inclusion of calcite saturation state (Ωc). High-resolution predictor generated best models and higher variables contribution. Important database and spatial analysis for rhodolith beds in Southwestern Atlantic.